2018
DOI: 10.4172/2167-0889.1000226
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Comparative Study of Spontaneous Peritonitis Associated with Fungal and Bacterial Infection in Patients with Liver Cirrhosis

Abstract: Objective: Although patients with liver cirrhosis (LC) have a high risk of developing bacterial and fungal infections, few studies have evaluated spontaneous fungal peritonitis (SFP) or fungiascites in this population. Accordingly, we conducted a retrospective comparative study of spontaneous peritonitis associated with fungal (SFP and fungiascites) or bacterial culture-positive ascites [spontaneous bacterial peritonitis (SBP) and bacterascites] in patients with LC.Methods: This study enrolled 73 patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…The reports of serum Cr level are also inconsistent. As in this series, some comparative studies reported no significant differences in serum Cr between SFP and SBP [6,7,10] or between spontaneous peritonitis with a fungus-positive ascitic culture and spontaneous peritonitis with a bacteria-positive ascitic culture [11,12]. However, Elkhateeb et al [9] found that serum Cr was significantly higher in SFP than in SBP (culture-negative neutrocytic ascites).…”
Section: Comparative Studies Between Spontaneous Peritonitis Due To Fmentioning
confidence: 54%
See 4 more Smart Citations
“…The reports of serum Cr level are also inconsistent. As in this series, some comparative studies reported no significant differences in serum Cr between SFP and SBP [6,7,10] or between spontaneous peritonitis with a fungus-positive ascitic culture and spontaneous peritonitis with a bacteria-positive ascitic culture [11,12]. However, Elkhateeb et al [9] found that serum Cr was significantly higher in SFP than in SBP (culture-negative neutrocytic ascites).…”
Section: Comparative Studies Between Spontaneous Peritonitis Due To Fmentioning
confidence: 54%
“…Regarding the severity of underlying disease, Gravito-Soares et al [6] reported no significant differences in the Child-Pugh and MELD scores between patients with SFP and SBP. Our previous study [7] also reported no significant differences in the Child-Pugh scores between SFP and culture-positive SBP. Bucsics et al [11] and our previous study [12] reported no significant differences in the Child-Pugh scores between spontaneous peritonitis with a funguspositive ascitic culture and spontaneous peritonitis with a bacteriapositive ascitic culture.…”
Section: Comparative Studies Between Spontaneous Peritonitis Due To Fmentioning
confidence: 69%
See 3 more Smart Citations